New Explorations in Plato's Theaetetus : Belief, Knowledge, Ontology, Reception - Zucca, Diego (Brill's Plato Studies Series, 2022)
What is knowledge? This fundamental question is treated with unprecedented depth by Plato in his Theaetetus, where it opens the path to many puzzles and issues we are still coping with in our days: what is the nature of perception, belief, justification, truth? Which objects can be properly known? How are we to account for cognitive mistakes? How can the mind be "in touch" with the world? This book provides fresh, rigorous and original explorations of the main themes of the dialogue by well-established scholars who work on Plato and Platonism, especially on Plato's theory of knowledge.